Characterisation of optimised supercritical carbon dioxide chia seed oil using tocopherol quantification, fatty acid profile, oxidation kinetic and digestion study - Ishak, Izzreen (2023)
Particle size affects the yield of seed oil extraction other than supercritical carbon dioxide (SC-CO2) parameters. Chia seed oil (CSO) extracted by supercritical fluid extraction (SFE) is vulnerable to oxidation which contains more than 80% polyunsaturated fatty acids (PUFA). However, limited study has been conducted on examining the effect of different particle sizes of chia seed in extracting a high yield of oil using SC-CO2. Therefore, the objectives of this study are: i) To determine the optimum SC-CO2 extraction parameters and particle size of the ground sample to extract the highest yield of CSO. ii) To compare the optimised CSO extracted by SCCO2 (SC-CO2-CSO) characteristics with Soxhlet (SOX-CSO) in terms of oxidation levels, tocopherols, PUFA, and oxidative stability. iii) To evaluate the oxidation stability of SC-CO2-CSO during storage with SOX-CSO. iv) To identify the bioaccessibility of tocopherols and volatile oxidation compounds of SC-CO2-CSO (fresh and stored) using in vitro stomach and small intestine. The optimisation parameters include different particle sizes of chia seeds based on grinding times (10-30 s) and SFE at different temperatures (40-80 °C) and pressure (220-340 bar) to maximise the CSO yield. The optimum yield (30.7%) of CSO based on Central Composite Design is similar to the predicted value (31.1%) at the pressure (335 bar), temperature (40 °C), and grinding time of chia seed (20 s). The oxidative stability shows both CSO (SC-CO2-CSO: 0.88 h and SC-CO2-SOX: 1.49 h) are less protected against oxidation due to the high amount of PUFA (85%) in CSO. For objective 3, the oxidation level, degradation of tocopherols, and antioxidant activity of SC-CO2-CSO and SOX-CSO stored at different temperatures (25-60 °C) were evaluated kinetically based on the reaction rate constant (k) and activation energy (Ea). The k for oxidation level (PV:0.047-0.468 mEq O2/kg oil day-1), degradation of antioxidant activity (0.000-0.552 % day-1) and α- (0.031-0.233 mg/kg oil day-1) and γ-tocopherols (0.003- 0.03 mg/kg oil day-1) of SC-CO2-CSO and SOX-CSO increased significantly (p<0.05) as storage temperatures increased from 25-60 °C. Lower Ea for the degradation rates of tocopherols (0.012-0.032) than antioxidant activity (147.429-149.26) and oxidation levels (52.779-54.756) in SC-CO2-CSO and SOX-CSO were obtained due to the tocopherol acted as a hydrogen donor to prevent oxidation during storage. As storage temperature increases, the shelf life of SC-CO2-CSO and SOX-CSO is decreased significantly (p<0.05) from 2.35 to 0.23 months. Finally, fresh (PV: 0.6 mEq O2/kg oil) and stored (PV: 26.7 mEq O2/kg oil) SC-CO2-CSO were submitted to the in vitro stomach and small intestine digestion models to determine the bioaccessibility of tocopherols and fatty acids, antioxidant activity and volatile oxidation compounds. Stored SC-CO2-CSO has significantly (p<0.05) higher concentration of aldehydes (2.58-12.29 Bp x 106), lower tocopherols (37.87-73.54%), α-linolenic acid (36.53- 89.97%) and antioxidant activity (6.6-12.6%) are prone to oxidation than fresh SCCO2- CSO using in vitro stomach and small intestine models due to occurrence of oxidation process. Therefore, fresh SC-CO2-CSO has higher bioaccessibility of PUFAs and tocopherols, antioxidant activity, and lower oxidation than stored SCCO2- CSO, which can be diversified as vegetable-based oil supplement and functional food ingredient.